Analisis Keterampilan Berpikir Kreatif Peserta Didik Kelas VIII SMP Kristen Seriti - Cristy Natalia Daniel; Muh. Tawil; Hasanuddin Hasanuddin (Universitas Negeri Makassar, 2026)
Creative thinking can be applied by students in all learning to hone their skills. Initial observations conducted at Sriti Christian Junior High School showed that students still experience limitations in creative thinking, so that students have difficulty in understanding the learning provided through a conventional learning system as mentioned by the 8th grade science teacher. The amount of creative thinking ability is measured through the average creative thinking ability in class VIII A and VIII B based on several indocators at Seriti Christian Junior High School, so that from this research, it can facilitate the school in designing learning strategies and can provide more effective facilities to support the creative thinking ability of students through a quantitative descriptive survey method. Through 5 items of essay indicator questions, the results of the creative thinking skills of students in class VIII of Seriti Christian Junior High School were 12.05 with a percentage of 43.13% in the moderately creative category, the average score of the analysis of creative thinking skills in class VIII A was 43.23% in the moderately creative category, the average score of the analysis of creative thinking skills in class VIII B was 43.04% which was in the moderately creative category, while the average score of students' creative thinking skills on the KBK (1) indicator was 30.68% as less creative, KBK (2) was 70.91 in the creative category, and KBK (3) was 27.80% so it was categorized as less creative.